Fluorescence-guided surgery for the treatment of medication-related osteonecrosis of the jaw: a prospective cohort study - Otto, Sven; Ristow, Oliver; Pache, Christoph; Troeltzsch, Matthias; Fliefel, Riham; Ehrenfeld, Michael; Pautke, Christoph (Journal of cranio-maxillofacial surgery, 2016)
Introduction - The delineation of the necrotic bone is a crucial step in the surgical treatment of medication-related osteonecrosis of the jaw (MRONJ). Several different approaches have been described including the innovative technique of fluorescence-guided surgery. However, until now there is a lack of data regarding the outcome. Therefore, the aim of the present study is to investigate the long-term success rates of fluorescence-guided surgery in the treatment of MRONJ. - Patients and methods - 54 Patients were prospectively assigned for surgical treatment of medication-related osteonecrosis of the jaw using fluorescence-guided surgery. Patients received doxycycline 100 mg twice a day for at least seven days preoperatively. Surgical treatment of MRONJ included complete removal of necrotic bone, which was monitored using the visual enhanced lesion scope (Velscope), followed by smoothening sharp bony edges and meticulous wound closure. Procedure success was assessed as postoperative maintenance of full mucosal coverage without pain, infection or bone exposure during regular follow-up. - Results - The study included a total of 54 patients (32 female and 22 male, mean age 71.4 ± 9.2 years). In the last follow-up an intact mucosa and absence of exposed bone, pain or signs of infection was identified in 47 of 54 patients (87%) and 56 of 65 lesions (86.2%) after first surgery using fluorescence-guidance. In 4 patients with 6 lesions a second fluorescence-guided surgery was necessary to achieve complete mucosal closure. Respectively, including the case with second surgical attempt 51 of 54 patients (94.4%) and 62 of 65 lesions (95.4%) showed complete mucosal healing. - Conclusion - The study shows that fluorescence-guided surgery is a safe and successful treatment option which can be considered for all stages of MRONJ. The technique seems also promising for MRONJ cases under denosumab.
Gesehen am 16.10.2020